FXYD5/Dysadherin, a Biomarker of Endometrial Cancer Myometrial Invasion and Aggressiveness: its Relationship With TGF-β1 and NF-κB Pathways - Besso, María José (2019)
Endometrial cancer (EC) is the second most common gynecological cancer worldwide. Myometrial invasion (MI) is a key event in EC dissemination. This study aimed to evaluate FXYD5/dysadherin (FXYD5/Dys) expression in EC tissue and uterine aspirate (UA) biopsies and to assess molecular/functional changes associated with its expression in cellular models.